PHASE STABILITY AND IONIC CONDUCTIVITY OF NASICON-LIKE PHASES IN SCPO4-NA3PO4 - LI3PO4 TERNARY SYSTEM - Zhuravleva M.; Novoselov A.; Yoshikawa A.; Fukuda T.; Zakalyukin R.; Fomichev V.; Zimina G. (My University, 2006)
Phase formation in ternary system of complex Sc, Na and Li phosphates was studied at 950°C and synthesis of new phases of definite composition was carried out. Obtained specimens were investigated with X-ray powder diffraction, infrared and impedance spectroscopy. Compositions of fields of homogeneity with NASICON-like structure were discovered. Temperature dependency of ionic conductivity was measured.
Keywords: PHASE DIAGRAM; PHOSPHATE; SOLID SOLUTION; SOLID-STATE ELECTROLYTE